Peningkatan Pengelolaan Keuangan Menggunakan Metode Kakeibo Pada Anak Panti Asuhan YPMS Tingkat SMP - Elizabeth Putri; Abdul Azis; Putri Malihul Hanny; Sofhya Cahyani; Putri Nurmala (Universitas Pamulang, 2023)
Community Service (PKM) carried out by students of the Faculty of Economics and Business in the Pamulang University Bachelor of Accounting Study Program is one of the activities carried out with the aim of helping the surrounding community in solving simple problems in everyday life in terms of academic understanding (socialization). as well as building a sense of socialist students towards the environment around the campus. In adolescents such as junior high school students it is still very difficult to manage small finances, so our group decided to raise this material with the intention that they would be able to better understand how good financial management is at their age and be able to apply how to implement good financial management so that they can useful in the future. kakeibowhere the method is a storage method with a priority scale. During the question and answer session, there were several children who had been saving for a long time and for the rest they were determined to save using the kakeibo method (priority scale method) because they had started to understand how to manage their small finances so that they would be more useful in the future and how important it is to have personal savings in the future because as time goes on, the needs that must be met also increase.Keywords : Savings; Kakeibo Method ; Financial Management